Multifactorial analysis to examine drivers of CMS summary star ratings in home health agencies. Issue 2 (3rd April 2019) - Zikos, Dimitrios; Massaria, Katelyn; Graziano, Marcello; DeLellis, Nailya
ABSTRACT: This cross-sectional study examines factors associated with the CMS Summary Star Ratings in Home Health Agencies (HHA). Using Home Health Compare, medical claims, and census data, negative binomial regression analysis was conducted at the HHA level. Positive associations were found between Summary Star Ratings and beneficiary age, the number of claims, the proportion for specific diagnoses, the agency being hospital based, HHA age since establishment, patient retainment, improved walking/moving/bathing, and homeownership. Negative associations were found for specific ICD diagnosis proportions, HHAs serving special populations, the rate of non-white patients, patients transferred to different HHAs, income, and marital status in the coverage area. These findings are relevant to both practitioners and policymakers, in that they highlight major non-service factors associated with perceived quality of care.